Pyruvate ingestion for 7 days does not improve aerobic performance in well-trained individuals - Morrison, M. A.; Spriet, L. L.; Dyck, D. J. (Journal of Applied Physiology, 2000)
The purposes of the present studies were to test the hypotheses that lower dosages of oral pyruvate ingestion would increase blood pyruvate concentration and that the ingestion of a commonly recommended dosage of pyruvate (7 g) for 7 days would enhance performance during intense aerobic exercise in well-trained individuals. Nine recreationally active subjects (8 women, 1 man) consumed 7, 15, and 25 g of pyruvate and were monitored for a 4-h period to determine whether blood metabolites were altered. Pyruvate consumption failed to significantly elevate blood pyruvate, and it had no effect on indexes of carbohydrate (blood glucose, lactate) or lipid metabolism (blood glycerol, plasma free fatty acids). As a follow-up, we administered 7 g/day of either placebo or pyruvate, for a 1-wk period to seven, well-trained male cyclists (maximal oxygen consumption, 62.3 ± 3.0 ml · kg1 · min1) in a randomized, double-blind, crossover trial. Subjects cycled at 74-80% of their maximal oxygen consumption until exhaustion. There was no difference in performance times between the two trials (placebo, 91± 9 min; pyruvate, 88 ± 8 min). Measured blood parameters (insulin, peptide C, glucose, lactate, glycerol, free fatty acids) were also unaffected. Our results indicate that oral pyruvate supplementation does not increase blood pyruvate content and does not enhance performance during intense exercise in well-trained cyclists.